The Influence of the eLDirU LMS, Digital Literacy, and CBL Methods on Learning Achievement - Dyah Perwita; Retno Widuri; Nur Choirul Afif (Economic Education Analysis Journal, 2023)
This research aims to analyze the influence of the eLDirU Learning Management System, Digital Literacy and Case Based Learning methods on learning achievement. This research uses a quantitative research approach and descriptive survey method with descriptive statistical data analysis techniques to analyze research data. Data collection techniques use observation methods, questionnaires, and documentation. This research was conducted at the Faculty of Economics and Business, Jenderal Soedirman University with the population are active students in the Faculty of Economics and Business that registered in the 2021-2022 academic year. Meanwhile, the sampling technique in this research used the cluster sampling and based on the calculation, there are 100 students as samples in this research. Data analysis techniques use instrument tests (validity test, reliability test, and path analysis, classical assumption test), model feasibility test, coefficient of determination test, simultaneous test, and hypothesis test (t test). The results of this research show that: (1) The Learning Management System partially has a significant effect on student learning achievement; (2) Digital Literacy partially has a significant effect on student learning achievement; and (3) Case Based Learning partially has a significant effect on student learning achievement. The conclusion of this research there is influence of learning management systems, digital literacy, case-based learning, on learning achievement simultaneously. This research is limited to external factors that influence learning achievement, namely leaning management system, digital literacy, and case-base learning method. Further research can analyze other factors that influence learning achievement, for example internal factors such as motivation, intelligence, and so on.